Patient involvement in psychological therapies for substance misuse: Towards a personalised outcome measurement - Alves, Paula Cristina Gomes (2016)
Patient involvement with healthcare provision is limited, particularly in treatment outcomes measurement. This is even more critical in substance misuse treatment, where patients tend to be stigmatised and their perspectives devalued. There are calls for a paradigm shift towards a greater patient involvement and personalisation of outcome measurement in substance misuse treatment. Responding to such call, this project implemented an idiographic outcome measurement approach in substance misuse treatment, through the use of individualised patient-reported outcome measures (I-PROMS). Unlike the traditional nomothetic method, which relies on standardised measures with pre-set items, I-PROMS are tailor-made tools with items created by patients, in their own words. I-PROMS do not only increase patient involvement with outcome measurement, by asking patients to actively contribute for the generation of items, but also permit a personalisation of measurement by focusing on topics of relevance for each individual case. The findings of our five articles showed that patients welcomed the freedom provided by I-PROMS to express their personal concerns, mainly in the presence of their therapists. I-PROMS allowed the identification of qualitative information that standardised measures targeting general psychological distress and drug-related problems missed to capture. On psychometrics, I-PROMS produced good reliable scores but were not strongly correlated with standardised outcome measures. Overall, our project suggests that, in substance misuse treatment, I-PROMS are a potential strategy to successfully increase patient involvement with outcome measurement and to personalise the evaluation of treatment outcomes. The combined use of I-PROMS with standardised measures is recommended for optimal results.